Advanced vessel sealing devices in total thyroidectomy for substernal goitre: A retrospective cohort study. (November 2016) - Testini, Mario; Pasculli, Alessandro; Di Meo, Giovanna; Ferraro, Valentina; Logoluso, Francesco; Minerva, Francesco; Pezzolla, Angela; Gurrado, Angela
Abstract: Introduction: When total thyroidectomy is performed for substernal goitre, a high risk of morbidity is reported. Advanced vessel sealing devices provide an alternative to the conventional clamp and tie technique. The aim of this study is to compare the outcome of patients who underwent total thyroidectomy for substernal goitre using Ligasure Small Jaw, Harmonic Focus, or conventional technique. Methods: Between 2011 and 2014, from a population of 393 patients undergoing surgery for thyroid disease, 75 (49 females, 26 males, mean age: 57.9 years; range: 28–83 years) underwent total thyroidectomy by the same surgeon for substernal goitre. Patients were divided into three groups: group A (n = 26) in which total thyroidectomy was performed using conventional technique; group B (n = 22), and group C (n = 27) in which total thyroidectomy was performed using Ligasure Small Jaw and Harmonic Focus, respectively. Operative time, time to drain removal, hospitalization and morbidity (hypoparathyroidism, vocal cord palsy, haemorrhage, seroma, other) were analyzed. Results: Mean duration of surgery was 136.5 ± 26.7 min in group A vs 110.5 ± 24.8 in B, and 101.6 ± 25.4 in C, with significant statistical differences between A vs B (p < 0.005) and C (p < 0.0001). There was no mortality. The overall morbidity was 29.3%. There was no significant difference in time to drain removal, postoperative hospitalization, and morbidity among the three groups. Conclusion: This is the first study analyzing advanced vessel sealing devices in total thyroidectomy for substernal goitre in the literature. The use of advanced vessel sealing devices significantly reduces operative time of total thyroidectomy performed for substernal goitre but does not seem to affect the other evaluated outcomes. Highlights: 75 patients underwent total thyroidectomy by the same surgeon for substernal goiter. Patients were divided in three groups, according to the used technique: "clamp and tie", Ligasure Small Jaw, Harmonic Focus. No difference among the groups in morbidity, duration of drain. Advanced vessel sealing devices shortened operative time.